Role Family in Handling Relapse in Mental Disordered Patients - Mawarti, Indah; Yusmahendra, Devi; Nasution, Riska Amalya; Yusnilawati, Yusnilawati; Meinarisa, Meinarisa (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
Relapse is an important problem that often recurs in patients with mental disorders. What often happens when the patient has returned to the family and community environment. The family as the closest person to the client is the main support system in providing direct services when the client is at home. Therefore the family has an important role in efforts to prevent recurrence of disease in mental clients. Seeing the phenomenon above, the purpose of this activity is so that families have an understanding of how to care for family members who experience mental disorders in the psychiatric clinic of the mental hospital in Jambi province. One of the efforts made is for nurses to carry out counseling to provide health education by gathering family members of patients who are waiting in the psychiatric poly clinic room. The counseling activity was attended by 28 participants, and during the activity the participants seemed enthusiastic in participating in the activity by asking questions related to the material provided. It is hoped that with the information provided, the role of the family in the prevention and treatment of recurrence in patients with mental disorders can be even better